DAMPAK PROGRAM PELATIHAN SOFT SKILLS TERHADAP PENINGKATAN KOMPETENSI KARYAWAN - Mardiman, Mardiman; Taufik, Taufik; Rasiwan, Iwan; Syahrial, Agan; Hendiyani, Rani; Kusuma, Aditya Bayu (Media Mahardhika, 2026)
This study aims to analyze the impact of soft skills training programs on improving employee competencies at Kartamulia University Purwakarta, focusing on employees who play crucial roles in daily administrative and operational services. Using a quantitative approach through an online survey of 45 respondents who had participated in the training and worked for at least three months after the training, data were collected through a Likert scale-based questionnaire and analyzed using simple linear regression with SPSS. The results of the study indicate that the soft skills training program has a positive and significant effect on improving employee competence, with a regression coefficient of 0.666 and a coefficient of determination (R²) of 49.8%. Hypothesis testing confirmed that this effect was statistically significant (t-count = 6.682 > t-table = 2.014; p = 0.000). Theoretically, this study provides originality by filling a gap in the literature on soft skills training for employees at private universities in Indonesia, a group that has received little attention in human resource development studies. This study also tested the application of the Kirkpatrick training evaluation model in the context of local educational organizations. From a practical perspective, these findings provide an empirical basis for university management to improve the design and implementation of soft skills training, as well as a reference for other universities, especially private ones.